1991
DOI: 10.1177/001872679104400601
|View full text |Cite
|
Sign up to set email alerts
|

Group Decision Fiascoes Continue: Space Shuttle Challenger and a Revised Groupthink Framework

Abstract: This paper reviews the decision situation surrounding the decision to launch the space shuttle Challenger in January 1986 in the light of the groupthink hypothesis. A revised framework is presented that proposes time and leadership style as moderators of the manner in which group characteristics lead to groupthink symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 5 publications
0
60
1
2
Order By: Relevance
“…In some cases, he argued, a high level of morale and commitment to the group can result in a sense of moral superiority and a stronger tendency to conform to the majority within the group. He called this phenomenon groupthink, which proposes that this high cohesiveness and desire for 155 Neck 1995, 156 Esser 1998, 157 Moorhead 1991, 158 Park 1990, 159 and Wekselberg 1996. 160 unanimity can override the group's ability to appraise alternative courses of action and result in poor-quality decision-making and decision errors.…”
Section: Background and Historymentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, he argued, a high level of morale and commitment to the group can result in a sense of moral superiority and a stronger tendency to conform to the majority within the group. He called this phenomenon groupthink, which proposes that this high cohesiveness and desire for 155 Neck 1995, 156 Esser 1998, 157 Moorhead 1991, 158 Park 1990, 159 and Wekselberg 1996. 160 unanimity can override the group's ability to appraise alternative courses of action and result in poor-quality decision-making and decision errors.…”
Section: Background and Historymentioning
confidence: 99%
“…127,128 Leadership Many reviews have found that the role of the leader can be a crucial variable in a group context, which may have important consequences for group decision processes and outcomes. 127,158,163,171 Overall, empirical studies have yielded relatively consistent evidence that groups with directive leaders use less of the available information, suggest fewer solutions and rate their leaders as more influential in the decision process than groups with non-directive leaders. 129,157,171 A directive style leader who states his or her opinion in a forceful way is less likely to foster the discussion of divergent opinions and hence may reduce the likelihood of reaching a good decision.…”
Section: Group Sizementioning
confidence: 99%
“…Another phenomenon that has been applied to the Challenger disaster that can also be applied to the breakdown at Abu Ghraib is the concept of groupthink (Moorhead, Ference, & Neck, 1991). Janis (1982), the father of groupthink, says it occurs when a cohesive group uses a flawed decision-making process in a stressful situation.…”
Section: State Crime: Normalization Of Ill-treatment and Torture At Amentioning
confidence: 99%
“…Groupthink is most likely to happen in settings where a highly cohesive group acts without qualified outside opinions. 57 By providing an outside point of view, volunteers can serve as devil' s advocates and prevent groupthink.…”
Section: The Advantages Of Using Volunteersmentioning
confidence: 99%